Persistent symptoms 3 months after a SARS-CoV-2 infection: the post-COVID-19 syndrome? - Goërtz, Yvonne M.J.; Van Herck, Maarten; Delbressine, Jeannet M.; Vaes, Anouk W.; Meys, Roy; Machado, Felipe V.C.; Houben-Wilke, Sarah; Burtin, Chris; Posthuma, Rein; Franssen, Frits M.E.; van Loon, Nicole; Hajian, Bita; et al. (ERJ open research, 2020)
Many patients with COVID-19 did not require hospitalisation, nor underwent COVID-19 testing. There is anecdotal evidence that patients with "mild" COVID-19 may complain about persistent symptoms, even weeks after the infection. This suggests that symptoms during the infection may not resolve spontaneously. The objective of this study was to assess whether multiple relevant symptoms recover following the onset of symptoms in hospitalised and nonhospitalised patients with COVID-19. A total of 2113 members of two Facebook groups for coronavirus patients with persistent complaints in the Netherlands and Belgium, and from a panel of people who registered on a website of the Lung Foundation Netherlands, were assessed for demographics, pre-existing comorbidities, health status, date of symptoms onset, COVID-19 diagnosis, healthcare utilisation, and the presence of 29 symptoms at the time of the onset of symptoms (retrospectively) and at follow-up (mean±sd 79±17 days after symptoms onset). Overall, 112 hospitalised patients and 2001 nonhospitalised patients (confirmed COVID-19, n=345; symptom-based COVID-19, n=882; and suspected COVID-19, n=774) were analysed. The median number of symptoms during the infection reduced significantly over time (median (interquartile range) 14 (11-17) 6 (4-9); p<0.001). Fatigue and dyspnoea were the most prevalent symptoms during the infection and at follow-up (fatigue: 95% 87%; dyspnoea: 90% 71%). In previously hospitalised and nonhospitalised patients with confirmed or suspected COVID-19, multiple symptoms are present about 3 months after symptoms onset. This suggests the presence of a "post-COVID-19 syndrome" and highlights the unmet healthcare needs in a subgroup of patients with "mild" or "severe" COVID-19.